Streamlining possibility of transport-supply logistics when using chosen Operations Research techniques - Stopka Ondrej (De Gruyter, 2020)
The subject of this article is to model and streamline processes in the area of the transport-supply logistics in a specific enterprise. The topic of the manuscript was implemented in a particular enterprise with the residence in the city of České Budějovice (South Bohemia region). The aim of the article is to step by step analyze the current state of the supply logistics of the specific subject and propose appropriate measures contributing to optimize the entire process using selected techniques of the Operations Research. By applying the methods of multi-criteria decision analysis (such as Weighted Sum Approach and Technique for Order Preference by Similarity to Ideal Solution), the most attractive option is chosen; i.e. the optimal supplier for the implementation of the transport-supply process that will enhance the effectiveness of specific logistics activities in the operation being examined. The conclusion in detail discusses individual contributions in terms of the suggested ways of modeling and improving the current state with respect to supply processes in the selected enterprise.